ISUW 2021 Proceedings of the 7th International Conference and Exhibition on Smart Energy and Smart Mobility for Smart Cities - Pillai, Reji Kumar; Singh, B. P.; Murugesan, N. (Lecture Notes in Electrical Engineering, 2022)
VIII, 496 p. 277 illus., 252 illus. in color.